The nuclear DEK interactome supports multi‐functionality. Issue 1 (11th November 2017) - Smith, Eric A.; Krumpelbeck, Eric F.; Jegga, Anil G.; Prell, Malte; Matrka, Marie M.; Kappes, Ferdinand; Greis, Kenneth D.; Ali, Abdullah M.; Meetei, Amom R.; Wells, Susanne I.
Abstract: DEK is an oncoprotein that is overexpressed in many forms of cancer and participates in numerous cellular pathways. Of these different pathways, relevant interacting partners and functions of DEK are well described in regard to the regulation of chromatin structure, epigenetic marks, and transcription. Most of this understanding was derived by investigating DNA‐binding and chromatin processing capabilities of the oncoprotein. To facilitate the generation of mechanism‐driven hypotheses regarding DEK activities in underexplored areas, we have developed the first DEK interactome model using tandem‐affinity purification and mass spectrometry. With this approach, we identify IMPDH2, DDX21, and RPL7a as novel DEK binding partners, hinting at new roles for the oncogene in de novo nucleotide biosynthesis and ribosome formation. Additionally, a hydroxyurea‐specific interaction with replication protein A (RPA) was observed, suggesting that a DEK‐RPA complex may form in response to DNA replication fork stalling. Taken together, these findings highlight diverse activities for DEK across cellular pathways and support a model wherein this molecule performs a plethora of functions.